KRITERIA KRIMINALISASI: ANALISIS PEMIKIRAN MOELJATNO, SUDARTO, THEO DE ROOS, DAN IRIS HAENEN - Valerian, Dion (Veritas et Justitia, 2022)
In criminal law, “criminalization” is defined as a process of determining certain conduct as a criminal offense through legislation. This doctrinal legal research article describes and analyzes the criteria for criminalization as promulgated by Moeljatno, Sudarto, Theo de Roos, and Iris Haenen. Moeljatno’s criteria are: 1) the conduct is harmful to the public, 2) criminalization is the primary means to deter the harmful conduct, and 3) the government’s ability to effectively enforce the criminal provision. Sudarto promulgates three criteria: 1) harmfulness of the conduct, 2) cost and benefit analysis, and 3) law enforcement burden. Furthermore, Theo de Roos’ six criteria are: 1) feasibility and motivation of harm, 2) tolerance, 3) subsidiarity, 4) proportionality, 5) legality, and 6) practical applicability and effectiveness. Lastly, based on de Roos’ typology Iris Haenen formulates three criteria: 1) primary criteria, which contains “threshold principles”: the conduct must be a) harmful and b) wrongful, 2) secondary criteria, which contains “moderating principles”: proportionality, subsidiarity, and effectiveness, and 3) legality criterion (lex certa). The criteria for criminalization can be employed by the legislators and general public in scrutinizing the feasibility of criminalization of a conduct, to ensure that only the conducts which meet all the criteria that can be criminalized. Only by doing so will the practice of criminalization adhere to the ultimum remedium principle and deter unnecessary criminalization and overcriminalization.